SVPNN-ARAS strategy for MCGDM under pentapartitioned neutrosophic number environment - Pramanik, Surapati (Serbian Journal of Management, 2023)
The aim of the paper is to extend the ARAS (Additive Ratio ASsessment) strategy to the single-valued pentapartitioned neutrosophic number environment which we call the SVPNN-ARAS strategy. The single-valued pentapartitioned neutrosophic number is the extension of fuzzy number and neutrosophic number. It comprehensively deals with uncertainty as it replaces indeterminacy with three independent entities, namely, contradiction, ignorance, and unknown. To develop a decision-making strategy, the arithmetic averaging operator for pentapartitioned numbers is defined and its basic properties are established. Single valued pentapartitioned number is a suitable mathematical tool to deal with uncertainty comprehensively. The SVPNN-ARAS strategy effectively evaluates and ranks feasible alternatives. In this paper, the ARAS strategy for multi-criteria group decision-making in a pentapartitioned neutrosophic number environment is developed. To demonstrate the applicability of the proposed strategy, a green supplier selection problem is solved and sensitivity analysis is performed to reflect the impacts of weighting of the decision makers and criteria on ranking the alternatives.